ChemInform Abstract: Prins Spirocyclization for the Synthesis of Spiro[isobenzofuran‐pyran] Derivatives. Issue 8 (February 2015) - Reddy, B. V. Subba; Kumar, Harish; Reddy, P. Sivaramakrishna; Singarapu, Kiran Kumar
Abstract This novel Prins spirocyclization gives a variety of the title compounds with high diastereoselectivities.